Can Entrepreneurial Thinking Help Innovation in Established Mature Technology Corporations? An Exploratory Study in a Power Sector Multinational Firm - Weber, Thomas Karl-Heinz (2012)
Just like nature, also technologies and industries, products and companies go through life cycles -- from 'birth' through maturity to 'death'. Innovativeness gives birth to new technologies and products, and innovation is written on the (business) storybook of many entrepreneurial undertakings and ventures. Those again appear habitually as starting or turning points in company and industry pedigrees. Further down the road, companies achieve maturity by managing consistently production and delivery. And management is supposed to do everything to keep things going that way. But maturity also poses a challenge as destiny can take over any time, following the life cycle timeline and owing to the ephemerality of products and technologies. Clinging to the proverbial 'milk cow' till the last drop could spell doom for the company. While it is possible to shift business by acquiring ready-to-run enterprises, the price is usually high and therefore rarely a feasible option. Hence, to ensure future, management of the 'going concern' has to deal with the renewal challenge by looking at innovation. On the strategic level, this brings together seeking competitive advantage with seeking opportunities and 'doing something about it'. Management concepts that encapsulate strategic and entrepreneurial decision-making are called 'strategic entrepreneurship' or 'corporate entrepreneurship'. The established company can resort to various ways for obtaining innovation, while the common basic managerial assignment and task includes entrepreneurial thinking and acting. One key point is: It is already entrepreneurial to include entrepreneurial activity – read: innovation - in the strategic planning by management, namely alongside the ongoing business operations. Ultimately, this can mean innovate DIY (do-it-yourself), or obtaining innovation from outside. This paper describes how an established corporation manages ongoing (mature) business as well as innovative transformation given the specific circumstances in its industry and markets, and how therefore entrepreneurial undertaking adds to the managerial task at hand. The methodology adopted in this study is a narrative approach based on interviews conducted with representatives from business and technology management circles of various units in the corporation's power business unit.The analysis links participants' thoughts and themes with arguments and concepts found in prevailing literature about life cycles, innovation, entrepreneurship and management. While my closing arguments may be debatable with respect to the research limitations, I strongly suggest established corporations (i) to scan for entrepreneurial opportunities in the wider technology environment, (ii) to run non-core activities (including those which could later become core) outside the corporation rules and bounds applied to core activities, and (iii) to bring embryonic, infantile and adolescent undertakings by the corporation or its business units in contact with the mature 'going concern' only at defined points.